PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T.; Chamberlain, John H.; Meigs, Walter B. (The Accounting Review, 1960)
Abstract The following problems were prepared by the Board of Examiners of the American Institute of Certified Public Accountants and were presented as the first half of the C.P.A. examination in accounting practice on November 4, 1959. One of the major problem includes The Hale-Haworth-Nye Partnership was formed in 1950 with partner Hale contributing the major portion of the capital, and partners Haworth and Nye providing the knowledge and experience necessary for the operation of the business. The Unstable Furniture Company commenced business operations on January 1,1957. All sales are made on installment contracts and inventory records are on a periodic basis. Contract receivables are kept separate by years. At the end of each year adjustments for unrealized and realized gross profits are made through a Deferred Gross Profit on Installment Sales account. The Stanger and Theeler Company established a non-contributing profit-sharing trust for its employees, effective January 1, 1956. Contributions to the trust have been determined to be allowable as a deduction on the company tax return.